TbSAP is a novel chromatin protein repressing metacyclic variant surface glycoprotein expression sites in bloodstream form Trypanosoma brucei. Issue 6 (28th February 2021) - Davies, Carys; Ooi, Cher-Pheng; Sioutas, Georgios; Hall, Belinda S; Sidhu, Haneesh; Butter, Falk; Alsford, Sam; Wickstead, Bill; Rudenko, Gloria
Abstract: The African trypanosome Trypanosoma brucei is a unicellular eukaryote, which relies on a protective variant surface glycoprotein (VSG) coat for survival in the mammalian host. A single trypanosome has >2000 VSG genes and pseudogenes of which only one is expressed from one of ∼15 telomeric bloodstream form expression sites (BESs). Infectious metacyclic trypanosomes present within the tsetse fly vector also express VSG from a separate set of telomeric metacyclic ESs (MESs). All MESs are silenced in bloodstream form T. brucei . As very little is known about how this is mediated, we performed a whole genome RNAi library screen to identify MES repressors. This allowed us to identify a novel SAP domain containing DNA binding protein which we called TbSAP. TbSAP is enriched at the nuclear periphery and binds both MESs and BESs. Knockdown of TbSAP in bloodstream form trypanosomes did not result in cells becoming more 'metacyclic-like'. Instead, there was extensive global upregulation of transcripts including MES VSG s, VSG s within the silent VSG arrays as well as genes immediately downstream of BES promoters. TbSAP therefore appears to be a novel chromatin protein playing an important role in silencing the extensive VSG repertoire of bloodstream form T. brucei .